ABOUT INFLUENCE OF TORCH PARAMETERS ON QUALITY OF HEATING OF BILLETS IN CHAMBER FURNACE WITH ONE-SIDED LATERAL HEATING - Kayukov , Yuri; Cheprasov , Alexander; Ivanov , Victor; Nasarenko , Irene (Scientific Journal "Metallurgy", 2020)
Numeral researches of influence of parameters of torch are executed on the high-quality indexes of heating of purveyances in a chamber of furnace with the one-sided lateral heating. It is set that in the investigational interval of relative length of torch Ln the maximal size of heat emission is characterize a torch at Ln = 0,1. At the increase of values of parameter Ln to 0,5 the insignificant decline of mastering of warmth purveyances is fixed, that it is related to expansion of area of the intensive burning down of fuel and diminishing of temperature overfall between a torch and surface of the heated purveyance. At Ln > 0,5 length of torch exceeds the sizes of working chamber of furnace, that is accompanied by the substantial decline of level of mastering of warmth and appearance of chemical underfiring of fuel. The impulsive mode of fuel provides the step change of length of torch from maximal to the minimum legitimate value, and, also allows to take advantage long torch in the period of self-control of furnace. Calculations allowed to set that for the torches of maximal length axial resultants thermal streams are oriented to the gas-rings, and for the torches of minimum length - toward development of torch. Comparative estimation of quality of heating of metal at impulsive and traditional modes of heating executed self-controls of identical duration upon completion of period. It is set that the impulsive serve of fuel provides the step change of length of torch from maximal to the minimum legitimate value, and, also allows to take advantage long torch in the period of self-control of stove. The presence of pulsating torch assists the decline of uneven distribution of temperature of steam-disengaging environment in the areas of stove and, respectively, increase of equitability of thermal streams on the surface of the heated purveyances. At the same time arrive at the increase of temperature in the last after motion of torch gas areas, that assists the increase of heatcontent of metal. Comparison of quality of heating of purveyances at the different modes of heating of furnace was shown by advantage of the pulse-mode, which consists in the practically double lowering of eventual value of overfull of temperature on the surface of metal in the moment of its out-put from a furnace.